1993
DOI: 10.3130/aijax.447.0_17
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF ASYMMETRIC AND UNEVEN THERMAL RADIATION ENVIRONMENTS UPON THE HUMAN BODY : In the case of constant operative temperature

Abstract: The purpose of this paper 重 s to evaluate the influence of asymmetric and uneven thermal radia ・ tion field upon the hum 尹 n body, Experiments were conducted under the fol ! owing conditions . Ten young male subjects in sedentary nude posture were exposed to eithteen kinds of thermal radiation field , The 出 ermal radiation field ' was set to Ieft ・ right side symmetry and left − right side asymmetry with the aim of ℃ onstaht operative temperature. It was found the foliowing :The infLu . ence of asymmetric ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Horikoshi et al [92] and Kurazumi et al [93] ran experiments with uneven and asymmetric subjects in the indoor environment and for an uneven asymmetric thermal radiation environment; the local thermal radiation was seen to affect the psychological response, showing that there is a fluctuation in this response.…”
Section: Thermal Manikin Modeling Of An Infantmentioning
confidence: 99%
See 1 more Smart Citation
“…Horikoshi et al [92] and Kurazumi et al [93] ran experiments with uneven and asymmetric subjects in the indoor environment and for an uneven asymmetric thermal radiation environment; the local thermal radiation was seen to affect the psychological response, showing that there is a fluctuation in this response.…”
Section: Thermal Manikin Modeling Of An Infantmentioning
confidence: 99%
“…Kurazumi et al [94] showed the parameters for uneven and asymmetric thermal environment factors that can be indicators with which to evaluate the effects on the human body of an uneven asymmetric thermal radiation environment. The effects of these parameters were shown to cause a large spread in the body's response.…”
Section: Thermal Manikin Modeling Of An Infantmentioning
confidence: 99%
“…Horikoshi et al [53] clarified that directional variations appear due to the influence of local thermal radiation on psychological responses of the body in unstable, asymmetric thermal radiation environments. Kurazumi et al [54] clarified the existence of parameters for unstable, asymmetric thermal radiation environments in thermal environment indices assessing body influences in unstable, asymmetric thermal radiation environments. A large variation was shown to occur in the physiological response due to the influence of these parameters.…”
Section: Relationship Between Etfe and Thermal Sensationmentioning
confidence: 99%
“…For that reason, even though the thermal environment was same, the subject reaction showed some directivity. Kurazumi et al [43,44] clarified that there is a part of skin where its skin temperature can easily be affected in unequal and asymmetric thermal radiation environment. In this research left part of the human body skin temperature was measured.…”
Section: Relationship Between Etfe and Mean Skin Temperaturementioning
confidence: 99%